Finite element modelling and experimental study of oblique soccer ball bounce - Rezaei, A.; Verhelst, R.; Van Paepegem, W.; Degrieck, J. (Journal of Sports Sciences, 2011)
In this study, we develop a finite element model to examine the oblique soccer ball bounce. A careful simulation of the interaction between the ball membrane and air pressure in the ball makes the model more realistic than analytical models, and helps us to conduct an accurate study on the effect of different parameters on a bouncing ball. This finite element model includes a surface-based fluid cavity to model the mechanical response between the ball carcass and the internal air of the ball. An experimental set-up was devised to study the bounce of the ball in game-relevant impact conditions. Ball speed, angle, and spin were measured before and after the bounce, as well as ball deformation and the forces during the impact. The finite element model has been validated with three different sets of data, and the results demonstrate that the finite element model reported here is a valuable tool for the study of ball bounce. After validation of the model, the effect of the friction coefficient on soccer ball bounce was studied numerically. Simulation results show that increasing the friction coefficient may result in reversal of the horizontal impact force.